Morphological responses of Bombax ceiba to habitat heterogeneity in Southwest China - Wang, Yanfang; Zhang, Yueping; Mao, Kaize; Li, Wei; Cheng, Xiping (Frontiers in Ecology and Evolution, 2023)
In order to cope with environmental changes, plants constantly adjust their morphological characteristics in order to adapt to changing environment. In the present study, populations of Bombax ceiba from Xishuangbanna and Yuanjiang Dry and Hot River Valley in Yunnan Province were selected as the research objects. Six tree structure factors, such as tree height and crown width, eight leaf trait factors, such as leaf area and leaf length, and several habitat factors, such as areaal topography, meteorology and soil nutrients, were measured. Structural equation model and variation decomposition method were applied to analyze the effects of various habitat factors on tree structure and leaf traits of B. ceiba, and to reveal its morphological responses to habitat heterogeneity. The results showed that there was a significant negative correlation between tree structure and leaf traits in the two study habitats (i.e., Mengla area and Yuanjiang area), and the correlation coefficient was -0.47 in Mengla area and -0.22 in Yuanjiang area. Both topographic and soil factors had positive effects on tree structure of the two habitats, and the topographic factors had a greater impact on tree structure than leaf traits. The main difference was that meteorological factors had a positive effect on tree structure of Mengla, but a negative effect on leaf traits, while Yuanjiang showed the opposite patterns. The variation analysis showed that the superposition of three environmental factors in Mengla area had a greater explanation power of tree structure and leaf traits than that in Yuanjiang area, and the topographic factors had the largest explanation power of tree structure in both areas, which reflected that fact that the characteristics of Mengla habitat imposed a greater influence on B. ceiba. The soil factors in Mengla area accounted for 20.1% of the leaf traits, while the meteorological factors in Yuanjiang area accounted for 11.6%. The results showed that leaf traits were sensitive to environmental differences. In general, the responses of B. ceiba to heterogeneous habitats is based on the specific performance of its resource utilization capacity. The research results can provide references for exploring the morphological responses of plants to heterogeneous habitats.